(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2010)
The Arene Candide Cave (Finale Ligure, Northern Italy) is considered one of the most important prehistoric site in Italy. The archaeological excavations conducted by the “Istituto Italiano di Paleontologia Umana” of Rome revealed 3 different horizons: an upper horizon with Holocene human presence dated from the Neolithic to the Byzantine period, and two underlying Pleistocene horizons with Gravettian and Epigravettian lithic artefacts. The stratigraphical sequence of the upper Palaeolithic is divided in two groups of strata separated by a depositional gap: the “P” complex, divided in 13 layers, dated from 25,620 to 18,560 years BP, and the 5 “M” layers dated between 11,750 and 9,980 years BP (14C non-calibrated dating). In this paper the fossil bone remains of bats from “M” layers are described. Fifteen taxa, divided into 3 families and 6 genera have been identified: Rhinolophus ferrumequinum, R. mehelyi, R. euryale, R. hipposideros, Myotis myotis, M. blythii, M. capaccinii, M. emarginatus, M. mystacinus s.l., Myotis sp. (small sized), Plecotus auritus s.l., Nyctalus lasiopterus, N. noctula, Barbastella barbastellus and Miniopterus schreibersii. Comments for each of these taxa on current ecological and geographical distributions are presented, together with some osteometric measures and recent data referred to Late Pleistocene fossils bats in Italy. Finally, the value of this bat tanathocoenoses as a microclimatic, environmental, and human activity indicators is discussed. SHORT NOTE